ANALISIS PERKEMBANGAN DAN PENGARUH TIPOGRAFI PADA SAMPUL MAJALAH BOBO TERHADAP KETERTARIKAN ANAK - Setiawan, Michelle Jacqueline; Sihombing, Riama Maslan (Wimba : Jurnal Komunikasi Visual, 2024)
Bobo Magazine has been in production since 1973 and there are thousands of Bobo magazines that have been published. Bobo magazine has a cover design that is unique and different from other magazines. Its unique design has its own charm for readers, especially children. One of the most important design elements in cover design communication is typography. This study aims to analyze the development of typography in Bobo magazine and determine its effect on children's interests. This research refers to the theory of four main typographic principles including legibility, readability, visibility, and clarity. This research method uses a qualitative approach, with data collected from the results of documentation, observation, and literature. From the results of the analysis, it is known that there is a change in the typography design on the cover of Bobo magazine with the application of better typographic principles. The use of correct and appropriate typographic principles makes Bobo magazine successful in attracting children's attention. Typographic design can communicate well to readers and can convey information well, clearly, and precisely.